Cognitive functions and anxiety among blue-collar workers in hospitals during COVID-19 pandemic - Abbas Mohammadi; Abbas Mohammadi; Leila Ibrahimi Ghavamabadi; Maryam Silavi; Behzad Fouladi Dehaghi; Behzad Fouladi Dehaghi (Frontiers Media S.A., 2022)
BackgroundThe rapid spread of COVID-19 poses a major threat to public health worldwide. Hospital blue-collar workers, like other health care workers, may be under severe physical and psychological stress. This psychological distress is mainly described as symptoms of anxiety and depression, stress and cognitive function. This study aimed to investigate the effects of anxiety on cognitive function among laundry and sterilization center workers in 4 hospitals during COVID-19 pandemic.MethodThis study has a cross-sectional design and it was conducted among health service workers who were occupied in health facilities (laundry and sterilization center) in 4 hospitals. In the present study, two questionnaires and a test were used to collect the data included a general health questionnaire (GHQ-28), a health anxiety index questionnaire (HAI-18) and a cognitive function test. Descriptive statistics and Spearman correlation coefficient by SPSS version 19 were used.ResultsThe results showed that the overall score of coronavirus anxiety in male and female workers was 38.72 ± 5.94 and 40.92 ± 4.11, respectively. The correlation between auditory attention and coronavirus anxiety is moderate and has a negative trend (P = 0.050, n = 50, and r = −0.315). Workers with higher anxiety expressed lower auditory attention. Also, correlation between visual attention and coronavirus anxiety was weak and negative (P = 0.032, n = 50, and r = −0.179).ConclusionThis study revealed that cognitive and psychological aspects of mental health can be affected by COVID-19 exposure and its due anxiety in blue-collar workers in hospitals. These findings indicate that purposeful supportive interventions should be implemented to promote workers' health and cognitive function.